The Convergence of Classical Punishment in Money Laundering: Follow the Money Principle Using Blockchain Approach - Efendi Lod Simanjuntak; Yuris Trinaili; Purwono; Muhamad Helmi Md Said (Lex Publica, 2025)
The application of corporal punishment to criminals is crucial for ensuring justice and legal certainty, as well as maintaining public order. However, in law enforcement regarding money laundering, there has been a shift in focus to asset recovery, based on the “follow the money” principle, which prioritizes the recovery of the proceeds of crime over punishing the perpetrator. This approach has the potential to cause disruption, as recovery of losses should only occur after the perpetrator is found guilty under criminal law. In the absence of adequate asset recovery regulations, blockchain can be a solution to strengthen the asset recovery process. This technology provides transparency and accountability in tracking asset flows and ensures data permanence. Blockchain enables more efficient and secure asset recovery, supporting a faster recovery process, and reducing the potential for compromise. Reconciling asset recovery approaches with corporal punishment is crucial for creating a balance in the justice system that goes beyond maintaining peace.